Thermal behavior of reusable ice cubes: Cooling efficiency and performance analysis - Luthfi, Luthfi (Jurnal Polimesin, 2025)
Reusable ice cubes as mini–ice packs have been widely used in the food industry and have played important roles in preventing waterborne diseases and microplastic contamination from using water ice cubes due to unhygienic water sources. This study investigates the thermal performance of various commercially available reusable ice cubes, assessing their cooling efficiency using a DS18B20 thermocouple sensor integrated with an Arduino microcontroller and a HIKMICRO B20 infrared camera. The primary objective is to evaluate and compare the cooling capabilities of different reusable ice cubes by measuring minimum temperatures and cooling times when placed in a water-filled glass. Experimental results indicate that stainless steel ice cubes exhibit faster cooling rates due to their higher thermal conductivity, whereas plastic ice cubes achieve lower minimum temperatures. The study further examines the influence of key parameters, including the number of ice cubes (N), water volume (V), and glass diameter (D). Empirical relationships for local plastic ice cubes were derived, showing dependencies of minimum temperature at Tmin ~ N1/5V1/3D5/2 and minimum cooling at tmin ~ N1/5V-1/5D3. These findings provide insights into the usage of reusable ice cube performance for various cooling applications.